Motif dan Kepuasan Masyarakat Kota Denpasar dalam Mengakses Portal Berita detikcom - Ayu Safitri, Ni Kadek Diah; Alit Suryawati, I Gusti Agug; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 2 (2019), 2019)
ABSTRACT detikcom is the most popular news portal in Indonesia which is accessed by more than 8.7 million Indonesians in a month. This7research7was7conducted7to7find7out7what7the motives and how the satisfaction the people of Denpasar in accessing detikcom. This study uses the TheoryIof1Uses and.Gratifications. The’type of this research is descriptive quantative method and the[samplingVtechniquesusedIwasJpurposive,sampling /technique. The.analytical technique:used in this research is descriptive statistics by looking at the mean score obtained of each motives and satisfaction the people of Denpasar in accessing detikcom. The result from this research showed, all of these four motives that can be satisfied by accessing detikcom.   Keywords: Denpasar, detikcom, Motives, Satisfaction, Society